2019
DOI: 10.1124/pr.118.016899
|View full text |Cite
|
Sign up to set email alerts
|

G Protein–Coupled Receptors in Asthma Therapy: Pharmacology and Drug Action

Abstract: Wendell et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 674 publications
(719 reference statements)
0
58
0
Order By: Relevance
“…To date, numerous clinical trials have shown that DP2 antagonists are effective for patients with asthma ( Figure 1) [153][154][155]. Fevipiprant (QAW039), an oral DP2 antagonist, improved pulmonary function in asthmatic patients with severely impaired lung functions and patients with uncontrolled asthma using an inhaled corticosteroid (ICS) [132,133,156].…”
Section: Asthmamentioning
confidence: 99%
“…To date, numerous clinical trials have shown that DP2 antagonists are effective for patients with asthma ( Figure 1) [153][154][155]. Fevipiprant (QAW039), an oral DP2 antagonist, improved pulmonary function in asthmatic patients with severely impaired lung functions and patients with uncontrolled asthma using an inhaled corticosteroid (ICS) [132,133,156].…”
Section: Asthmamentioning
confidence: 99%
“…β-adrenergic receptors (β-ARs) are the most structurally and pharmacologically studied subgroup of GPCRs [ 15 , 16 ]. They are also important drug targets, where both beta- mimetics and beta-blockers are employed in therapies of various conditions [ 17 , 18 , 19 ]. One of the first structurally evident instances of biased agonism at the β-AR system was characterized for bucindolol, carvedilol and nebivolol.…”
Section: β-Adrenergic Receptorsmentioning
confidence: 99%
“…In the context of the recent COVID-19 pandemic, Zhou et al [7] suggested that angiotensin receptor blockers may have the potential of inhibiting viral entry and can be considered as a prospective repurposable drug for 2019-nCoV/SARS-CoV-2. Many therapeutics used to either enhance bronchodilation or prevent bronchoconstriction for treating respiratory diseases including asthma are known to target β 2 -adrenergic receptors [8,9] and modulate Ca 2+ -signaling [10]. In this context, a more profound knowledge of the role and mechanism through which cytosolic Ca 2+ is regulated by GPCRs can help in curing these diseases.…”
Section: Introductionmentioning
confidence: 99%